Used of Probiotic Production of Saccharomyces boulardii to Eradication Triple Therapy of Helicobacter pylori Infection - Haamadi, Amer A; Risan, Mohsen Hashim; AboAlmaali, Hassan M.; Sayah, Hadi A.; Abbas, Ahmed H. (Scientific Journal of Medical Research, 2021)
Objectives: Detection of the H. pylori infection by demonstrating BabA gene and expression level of this gene during mice infection, with study the effect of probiotics extract and histopathological study on mice tissue change after infection and treatment. Methods: Out of 112 patients suffering from dyspepsia attending Al- Husain medical city / digestive system diseases center, Karbala city. Detection of Helicobacter pylori and also used probiotics yeast cell of Saccharomyces boulardii to eradicate antibiotic treatment of H. pylori infection. Study histological study on infected Lab animals with H.pylori treated with S. boulardii. Results: This study used probiotics yeast cell of Saccharomyces boulardii to eradicate antibiotic treatment of Helicobacter pylori infection. This appears through expression level BabA gene from a clinical isolate of these bacteria, and histological study on infected Lab animals with H.pylori treated with S. boulardii. The probiotic role was shown in the results to the eradication of antibiotic therapeutic Helicobacter infection. This appeared through an expression study of BabA gene in mice after infection with H. pylori bacteria and comparison between the expression level of this gene after therapy with antibiotic alone and treatment with antibiotics with probiotic. The expression level of the normal BabA gene of H. pylori in infected mice was 32.31. This was reduced to the 4.038 after treatment with antibiotics. This level of expression of gene was reduced to 0.504 after treatment with antibiotics probiotics. The role of probiotics also appeared in a histopathological study in mice biopsy when compared tissues after treatment with antibiotics and after treatment with antibiotics with probiotics. The present study proves that the probiotic yeast cell used for eradication role to the increase the effective treatment of H. pylori by antibiotics as the result mention. Conclusion: The present study proves the probiotic yeast S. boulardii used for eradication role of the increase the effective treatment of H. pylori by antibiotics. There were many methods used to diagnosis H. pylori infection, PCR sensitive one and especially when used more than one gene duplex PCR.